2011
DOI: 10.1080/15459624.2011.576330
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Semi-Empirical Two-Zone Dust Exposure Model for a Dusty Construction Trade

Abstract: Drywall finishing is a dusty construction activity. We describe a mathematical model that predicts the time-weighted average concentration of respirable and total dusts in the personal breathing zone of the sander, and in the area surrounding joint compound sanding activities. The model represents spatial variation in dust concentrations using two-zones, and temporal variation using an exponential function. Interzone flux and the relationships between respirable and total dusts are described using empirical fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Workers had dedicated tasks (bifurcated crew), and the finishing worker was a union member. Site 2 (Study A in Jones et al …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Workers had dedicated tasks (bifurcated crew), and the finishing worker was a union member. Site 2 (Study A in Jones et al …”
Section: Methodsmentioning
confidence: 99%
“…Here we integrate previous work to characterize cumulative exposures to dusts and asbestos fibers resulting from the sanding of joint compound during drywall finishing. Specifically, we apply a semi‐empirical mathematical model to predict 8‐h TWA respirable dust concentrations from joint compound sanding activities . These predictions are coupled with an empirical factor that relates chrysotile asbestos fiber to respirable dust concentrations to predict 8‐h TWA asbestos fiber concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…One study has been published using the same JCN as tested in the bench‐scale chamber that provides personal breathing‐zone respirable dust mass concentrations, C M‐rd , during sanding. ( 13 ) Due to the number of data points available ( N = 5) for the tested JCN, four additional published studies ( 2,12,14‐16 ) were identified that report C M‐rd values during sanding of other modern‐day joint compounds (Table I). To apply the new procedure to respirable dust data from these five published studies, we have assumed minimal variation in the characteristics (including emission rates) of the tested JCN and other modern‐day joint compounds in the other four studies.…”
Section: Methodsmentioning
confidence: 99%
“…Because respirable dust samples used in the new procedure are also task‐ or shift‐duration TWAs, ( 2 , 12‐16 ) it would be ideal if the short‐term or peak PCM fiber concentration distributions from F79VM80 were adjusted to “shift‐TWA” equivalent values before fiber concentration estimates based on historical data were compared to those based on the new procedure. Although there are no historical studies that report both peak and shift‐TWA fiber concentrations for workers sanding joint compound, Epling et al .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation